Exploring Islamic Moderation in Indonesia: A Bibliometric Approach to Systematic Literature Review - Lukman Taufik; M. M. Syamsurrijal (Tabéq Care Center and UIN Mataram, 2026)
Islamic moderation in Indonesia is examined in this study, reflecting its growing importance amid increasing radicalization and socio-political challenges in the region. A systematic literature review and bibliometric analysis are utilized to assess publication trends, key themes, and collaboration networks within the field of Islamic moderation. The methodology includes quantitative analysis of publications indexed in Scopus and S.I.N.T.A., as well as qualitative synthesis of findings from the existing literature. Results demonstrate a marked rise in publications on Islamic moderation, with dominant themes in politics, education, and economics, and reveal extensive collaboration among local and international scholars. The findings underscore the need for a more comprehensive theory of Islamic moderation, offer recommendations for addressing gaps in the literature, and suggest strategies for policymakers to enhance the implementation of Islamic moderation. Additionally, the study identifies prospects for expanded international collaboration, providing insights that may inform global initiatives to foster moderate values and tolerance.